Mice lacking multidrug resistance protein 1a show altered dopaminergic responses to methylenedioxymethamphetamine (MDMA) in striatum - Scheidweiler, Karl B. (2009)
Multidrug resistance protein 1a (MDR1a) potentiated methylenedioxymethamphetamine (MDMA)-induced decreases of dopamine (DA) and dopamine transport protein in mouse brain one week after MDMA administration. In the present study, we examined if mdr1a wild-type (mdr1a +/+) and knock-out (mdr1a −/−) mice differentially handle the acute effects of MDMA on the nigrostriatal DA system 0–24 h following a single drug injection. 3-way ANOVA revealed significant 2-way interactions of strain X time (F(5,152)= 32.4, p< 0.001) and strain X dose (F(3,152)= 25.8, p< 0.001) on 3,4-dihydroxyphenylacetic acid (DOPAC)/DA ratios in mdr1a +/+ and −/− mice. 0.3–3 h after 10 mg/kg MDMA, DOPAC/DA ratios were increased in mdr1a +/+ mice, but decreased 0.3–1 h after MDMA in mdr1a −/− mice. 24 h after 10 mg/kg MDMA, DOPAC/DA ratios were increased 600% in mdr1a +/+ mice compared to saline-treated control mice, while in mdr1a −/− mice DOPAC/DA ratios were unchanged. Striatal MDMA and its metabolite, methylenedioxyamphetamine, concentrations by gas chromatography-mass spectrometry were similar in both strains 0.3 to 4 h after MDMA, discounting the role of MDR1a-facilitated MDMA transport in observed inter-strain differences. Increased DOPAC/DA turnover in mdr1a +/+ mice following MDMA is consistent with the previous report that MDMA neurotoxicity is increased in mdr1a +/+ mice. Increased DA turnover via monoamine oxidase in mdr1a +/+ vs −/− mice might increase exposure to neurotoxic reactive oxygen species.